Corporate Social Responsibility in Polish Logistics Companies - Renata PIĘTOWSKA-LASKA (Communications of International Proceedings, 2021)
The article analyses the role and importance of Corporate Social Responsibility (CSR) for contemporary enterprises on the example of Polish logistics companies. The analysis focuses on the essence and scope of Corporate Social Responsibility, and methods of implementing the principles of sustainable development, sustainable and responsible supply chain management, and especially the principles of green logistics and Corporate Social Responsibility in relations with the social environment, in logistics enterprises. The aim of the study was to diagnose current trends and approaches of logistics companies in Poland in terms of Corporate Social Responsibility. The survey was conducted by means of questionnaire interviews in small (companies employing up to 49 persons), medium (companies employing 50-249 persons), and large (companies employing over 250 persons) logistics companies, represented by people responsible for managing sustainable and responsible business (directors, CEOs, board members, CSR specialists). The survey was conducted on a sample of 230 logistics organisations between 2018 and 2020. The findings of the study lead to the conclusion that socially responsible logistics consists in the implementation of tools to assess suppliers in terms of their compliance with social and environmental criteria, implementation of codes of ethics and conduct, operating procedures and integrated programs based on continuous improvement.
Keywords: Corporate social responsibility; logistics companies; socially responsible logistics; sustainable and responsible supply chain management.